The primary transcriptome of Neisseria meningitidis and its interaction with the RNA chaperone Hfq. Issue 10 (17th March 2017) - Heidrich, Nadja; Bauriedl, Saskia; Barquist, Lars; Li, Lei; Schoen, Christoph; Vogel, Jörg
Abstract: Neisseria meningitidis is a human commensal that can also cause life-threatening meningitis and septicemia. Despite growing evidence for RNA-based regulation in meningococci, their transcriptome structure and output of regulatory small RNAs (sRNAs) are incompletely understood. Using dRNA-seq, we have mapped at single-nucleotide resolution the primary transcriptome of N. meningitidis strain 8013. Annotation of 1625 transcriptional start sites defines transcription units for most protein-coding genes but also reveals a paucity of classical σ70-type promoters, suggesting the existence of activators that compensate for the lack of −35 consensus sequences in N. meningitidis . The transcriptome maps also reveal 65 candidate sRNAs, a third of which were validated by northern blot analysis. Immunoprecipitation with the RNA chaperone Hfq drafts an unexpectedly large post-transcriptional regulatory network in this organism, comprising 23 sRNAs and hundreds of potential mRNA targets. Based on this data, using a newly developed gfp reporter system we validate an Hfq-dependent mRNA repression of the putative colonization factor PrpB by the two trans-acting sRNAs RcoF1/2. Our genome-wide RNA compendium will allow for a better understanding of meningococcal transcriptome organization and riboregulation with implications for colonization of the human nasopharynx.